2011
DOI: 10.1369/0022155411418829
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Claudins and Their Prognostic Significance in Noninvasive Urothelial Neoplasms of the Human Urinary Bladder

Abstract: The members of the claudin family are major integral transmembrane protein constituents of tight junctions. Normal and neoplastic tissues can be characterized by unique qualitative and quantitative distribution of claudin subtypes, which may be related to clinicopathological features. Differential diagnosis and prognosis of nonmuscle invasive tumor entities of urinary bladder epithelium are often challenging. The aim was to investigate the expression profile of claudins in inverted urothelial papillomas (IUPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…A number of studies reported the overexpression of claudin-4 in a variety of cancers [12,14,[17][18][19][20][21][22][23]. The claudin-4 up-regulation was shown to stimulate MMP-2 activity in ovarian carcinoma cells and promote cancer invasion [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported the overexpression of claudin-4 in a variety of cancers [12,14,[17][18][19][20][21][22][23]. The claudin-4 up-regulation was shown to stimulate MMP-2 activity in ovarian carcinoma cells and promote cancer invasion [36].…”
Section: Discussionmentioning
confidence: 99%
“…The claudin-4 expression was up-regulated in several cancers, including esophageal, gastric, colorectal, pancreatic, ovarian, urothelial, breast, endometrial and prostate cancers [12,14,[17][18][19][20][21][22][23]. Its role in the invasiveness and survival of ovarian cancer cells has also been suggested in an in vitro study [24].…”
Section: Introductionmentioning
confidence: 99%
“…A connection between tight junctions in the maintenance of integrity of urothelium and prevention of recurrence of UCC was recognized in 1996 . Szekely et al executed an immunohistochemical study of the expression of claudin 1, 2, 4 and 7 in 15 IPs, 20 urothelial papillomas, 20 PUNLMPs and 20 low grade UCCs . Semi‐quantitative scores of staining intensity multiplied with predefined area‐positivity were calculated for each reaction and revealed that the claudin‐1 expression in urothelial papillomas, PUNLMP and low‐grade UCC was significantly reduced compared to IP.…”
Section: Molecular Changes In Ipmentioning
confidence: 99%
“…Claudin 1,4 and 7 are important members of this Claudin protein family and their expressions show alterations in many different malignancies such as oesophageal, gastric, biliary (Usami et al, 2006;Agarwal et al, 2009;Kwon et al, 2011), ovarian (Kwon et al, 2010), endometrial (Pan et al, 2007;Knoecny et al, 2008), bladder (Boireau et al, 2007;Szekely et al, 2011) renal (Lechpammer et al, 2008), prostate (Landers et al, 2008), breast (Kominsky et al, 2003), cholangiocarcinoma (Bunthot et al, 2012) and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%